COMBINED TREATMENT OF TEMPORO-MANDIBULAR JOINT DYSFUNCTION USING BITE PLATES BY ASSELMEYER - Shylenko, D.R.; Marchenko, A.V.; Eihgorn, T.Yu.; Pisarenko, O.A.; Gutarev, A.O. (World of Medicine and Biology, 2012)
In the is presented the substantiation of the algorithm of treatment of patients with combined tempero-mandibular joint dysfunction and neurological-like pain which is demand lamina-therapy by bites lamine by Asselmeyer before orthopedic and therapeutic occlusion-correction treatment to confirm its validity and early removal of its painful symptoms.
Keywords: occlusion; temporo-mandibular joint; bite plate; neuralgia